Neonate with Severe Complications of Epidermolysis Bullosa and Bilateral Clubfoot: An Unusual Case Presentation and Treatment - Krasniqi-Daka, Afërdita; Sejdiu-Hasbahta, Teuta; Gërçari, Antigona; Vuniqi-Krasniqi, Merita; Daka, Qëndresë (Journal of Nepal Paediatric Society, 2016)
Epidermolysis bullosa is a term for a heterogeneous group of rare disorders, characterized by extensive blistering of the skin and mucous membranes as the most prominent features. So far association of the disease with extra-cutaneous manifestations and complications has been pointed out. We present an unusual case of a neonate with severe complications of epidermolysis bullosa, associated with bilateral clubfoot. J Nepal Paediatr Soc 2015;35(2):181-184